Alpinetin alleviates osteoporosis by promoting osteogenic differentiation in BMSCs by triggering autophagy via PKA/mTOR/ULK1 signaling. (14th September 2022) - Zeng, Chenying; Wang, Shan; Chen, Fenglei; Wang, Ziming; Li, Jinteng; Xie, Zhongyu; Ma, Mengjun; Wang, Peng; Shen, Huiyong; Wu, Yanfeng
Abstract: Osteoporosis, a systemic bone disease that is characterized by a reduction in bone mass and destruction of bone microstructure, is becoming a serious problem worldwide. Bone marrow mesenchymal stem cells (BMSCs) can differentiate into bone‐forming osteoblasts, and play an important role in maintaining homeostasis of bone metabolism, thus being a potential therapeutic target for osteoporosis. Although the phytochemical alpinetin (APT) has been reported to possess a variety of pharmacological activities, it is still unclear whether APT can influence the osteogenic differentiation of on BMSCs and if it can improve osteoporosis. In this study, we found that APT treatment was able to enhance osteogenic differentiation levels of human BMSCs in vitro and mouse ones in vivo as revealed by multiple osteogenic markers including increased alkaline phosphatase activity and osteocalcin expression. Mechanistically, the protein kinase A (PKA)/mTOR/ULK1 signaling was involved in the action of APT to enhance the osteogenic differentiation of BMSCs. In addition, oral administration of APT significantly mitigated the bone loss in a dexamethasone‐induced mouse model of osteoporosis through strengthening PKA signaling and autophagy. Altogether, these data demonstrate that APT promotes osteogenic differentiation in BMSCs by augmenting the PKA/mTOR/ULK1 autophagy signaling, highlighting its potential therapeutic application for treating osteoporotic diseases.